2006
DOI: 10.1113/expphysiol.2005.031070
|View full text |Cite
|
Sign up to set email alerts
|

Whole heart action potential duration restitution properties in cardiac patients: a combined clinical and modelling study

Abstract: Steep action potential duration (APD) restitution has been shown to facilitate wavebreak and ventricular fibrillation. The global APD restitution properties in cardiac patients are unknown. We report a combined clinical electrophysiology and computer modelling study to: (1) determine global APD restitution properties in cardiac patients; and (2) examine the interaction of the observed APD restitution with known arrhythmia mechanisms. In 14 patients aged 52-85 years undergoing routine cardiac surgery, 256 elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 52 publications
9
119
1
Order By: Relevance
“…13 left panel, express the APD as a function of the RR interval (inverse of HR) for different regions within the myocardium. In experimental, clinical and computational studies, it has been shown that an increase in APDR dispersion is associated with greater propensity to suffer from VT/VF, the most common sequence to SCD [25], [26]. Other studies have reported differences in transmural heterogeneity at different cycle lengths between end-stage failing and non-failing human ventricles [27].…”
Section: B Abnormal Repolarization and Cardiac Arrhythmias 1) Patholmentioning
confidence: 99%
See 1 more Smart Citation
“…13 left panel, express the APD as a function of the RR interval (inverse of HR) for different regions within the myocardium. In experimental, clinical and computational studies, it has been shown that an increase in APDR dispersion is associated with greater propensity to suffer from VT/VF, the most common sequence to SCD [25], [26]. Other studies have reported differences in transmural heterogeneity at different cycle lengths between end-stage failing and non-failing human ventricles [27].…”
Section: B Abnormal Repolarization and Cardiac Arrhythmias 1) Patholmentioning
confidence: 99%
“…13), therefore providing potentially relevant information for ventricular arrhythmic risk stratification [25], [115]. Heterogeneities in the ventricle lead to non-uniform restitution properties, which makes APDR curves present spatial variations [116].…”
Section: ) Repolarization Dispersion By T-peak To T-end Interval Dynmentioning
confidence: 99%
“…To characterize the convergence in space and time of each of the simulation codes, the benchmark problem was solved using combinations of discretizations of the order of those used in the literature. The problem was solved at three spatial (Dx = 0.5, 0.2 and 0.1 mm [33][34][35][36]) resolutions, and each spatial resolution was then solved with three different partial differential equation (PDE) time steps (Dt = 0.05, 0.01 and 0.005 ms [33,34,36,37]), resulting in nine simulation results in total per simulation code applied to the benchmark problem.…”
Section: (D) Numerical Methodsmentioning
confidence: 99%
“…The LR-I is an established mathematical model for cardiac excitation generation in mammalian ventricular cell. This model is chosen because it well described the six ionic currents that retain enough structure of basic currents involved in cardiac excitation to reproduce exact AP morphologies [11] and the model is flexible enough that the parameters can be fitted to replicate accurately the properties and dynamics of other complex ionic models as well as experimental data [12][13] such as action potential duration (APD), thresholds for excitation, upstroke velocities, minimum APD before reaching conduction block, and phase-locking response characteristics to current stimulations. The FPGA implementation in the simulation cardiac excitation model under the voltage clamp is conducted by using the MATLAB Simulink through HDL Coder that gives an opportunity in obtaining Hardware Description Language (HDL) code by using an automatic code generation process without traditionally coding of the HDL code [9].…”
Section: Methodsmentioning
confidence: 99%